Telomere length in poor-risk chronic lymphocytic leukemia: associations with disease characteristics and outcome - Steinbrecher, Daniela; Dreger, Peter (Leukemia and lymphoma, 2018)
Telomere length in chronic lymphocytic leukemia (CLL) is described as an independent prognostic factor based largely on previously untreated patients from chemotherapy based trials. Here, we studied telomere length associations in high-risk, relapsed/refractory CLL treated with alemtuzumab in the CLL2O study (n = 110) of German and French CLL study groups. Telomere length (median 3.28 kb, range 2.52-7.24 kb) was relatively short, since 84.4% of patients had 17p- which is generally associated with short telomeres. Median telomere length was used for dichotomization into short and long telomere subgroups. Telomere length was associated with s-TK (p = .025) and TP53 mutations (p = .050) in untreated patients, while no association with clinical/biological characteristics was observed in relapsed/refractory CLL. Short telomeres had significant association with shorter PFS (p = .018) only in refractory CLL. Presence of short telomeres, loss of genes maintaining genomic integrity (SMC5) and increased incidence of chromothripsis, indicated the prevalence of genomic instability in this high-risk cohort.